Basic School Ghanaian Language Teachers' Perspectives on the Integration of ICTs in Teaching and Learning - Ernest Nyamekye; Daniel Baffour-Koduah; Esther Asare (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2021)
This study sought to explore Basic School Ghanaian Language teachers' perceptions of ICT integration in Ghanaian language teaching. The study employed the explanatory sequential mixed method design. Stratified random sampling was used to obtain data from 205 teachers in the Bono, Bono East and Ahafo region of Ghana. Analysis of data collected through a self-developed questionnaire and a semi-structured interview guide reveals that Ghanaian language teachers exhibit a positive perception of ICT integration in education. However, in practice, they tend to integrate ICT into their instruction on an occasional basis. Also, it was revealed that lack of financial support for ICT resources and lack of in-service training are factors that militated against ICT integration in Ghanaian language teaching. Finally, the study revealed a statistically significant difference between degree and diploma holders' perceptions of ICT integration in teaching and learning